Exploring Organizational Motivation for Implementing Big Data Analytics: A Systematic Literature Review - Suroto, Suroto (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The objective of this study is to gain insights into the motivations behind organizations in adopting Big Data Analytics (BDA) by conducting a systematic literature review that provides the key determinants of BDA implementation in different sectors. This study follows the PRISMA guidelines using the PICOC principle to formulate research questions and establish inclusion criteria, and involves a systematic literature search followed by analysis to synthesize findings related to motivations for BDA adoption across sectors. The results of this study on the different sectors, including manufacturing, the public sector, Healthcare, education, and retail, have revealed that operational efficiency, product innovation, data management, and the management support of the organization act as the motivating factors in any BDA adoption decision. This study concludes that the motivation for BDA adoption across sectors is influenced by factors such as technological capabilities, organizational support, environmental pressures, and economic incentives, with specific differences in each sector indicating unique challenges and benefits, and offers a basis for further research and practical applications in the field of BDA.